2016
DOI: 10.1002/bip.22768
|View full text |Cite
|
Sign up to set email alerts
|

C‐terminus of a hexapeptidic ghrelin receptor inverse agonist can switch peptide behavior from inverse agonism to agonism

Abstract: Subtle changes in the sequence at the N-terminus and in the aromatic core of hexapeptidic ghrelin receptor inverse agonists can switch behavior from inverse agonism to agonism, but the C-terminal role of the sequence is unclear. Thus, analogs of the ghrelin receptor inverse agonist KbFwLL-NH2 (b = β-(3-benzothienyl)-d-alanine) were synthesized by solid phase peptide synthesis in order to identify the influence of aromaticity, charge, and hydrophobicity. Potency and efficacy of the hexapeptides were evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Ghrelin served as control with an EC 50 of 1.0 nM (pEC 50 = 9.00 ± 0.05, E max = 100% ± 3%), which was comparable to data from previous experiments [49,50]. All compounds were found to be partial agonists at the GhrR with similar potencies in the low nanomolar range.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Ghrelin served as control with an EC 50 of 1.0 nM (pEC 50 = 9.00 ± 0.05, E max = 100% ± 3%), which was comparable to data from previous experiments [49,50]. All compounds were found to be partial agonists at the GhrR with similar potencies in the low nanomolar range.…”
Section: Resultssupporting
confidence: 84%
“…Unlabeled ghrelin served as control with an IC 50 of 1.7 nM, comparable to previous experiments [50]. ( S )- 9 was the starting compound for modification with an IC 50 of 2.2 nM (Figure 1A).…”
Section: Resultssupporting
confidence: 71%
“…For the assay, COS‐7 cells stably expressing the ghrelin receptor were used, and after stimulation with the peptide, the intracellular generation of IPs by the Gα q/11 signaling pathway of the GhrR was determined. Measurements were normalized to the control peptide ghrelin, which possesses a high potency at the GhrR (EC 50 = 1 nM) in accordance with previous studies . Peptide 8 was found to be a super‐agonist for the GhrR with nanomolar potency and a higher maximal receptor activation (E max = 135%) compared with ghrelin.…”
Section: Resultsmentioning
confidence: 55%
“…However, the additional phenyl side chain may regain the lost activity. Leu 5 of KbFwLL‐NH 2 was recently replaced by amino acids with various characteristics and it was shown that Lys, Gln, Phe, and Ala can induce agonism . The most efficient agonist was the d ‐2Nal 5 analogue, whereas 2Nal 5 had no activity at the ghrelin receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the d ‐2Nal 4 analogue 19 was 4‐fold more active than the Wrf 4 analogue ( 13 ), but the differences were diminished in the combined agonist. d ‐2Nal possesses strong agonism‐prone characteristics at position 4 and can even turn the efficient inverse agonist KbFwLL‐NH 2 ( 15 ) into an agonist by substitution of Leu 5 . It is surprising that 20 can almost reach the same activity as 18 .…”
Section: Resultsmentioning
confidence: 99%